2007
DOI: 10.3727/000000007783464687
|View full text |Cite
|
Sign up to set email alerts
|

Huntington's Disease: Pathological Mechanisms and Therapeutic Strategies

Abstract: Huntington's disease (HD) is a devastating neurodegenerative disorder that occurs in patients with a mutation in the huntingtin or IT15 gene. Patients are plagued by early cognitive signs, motor deficits, and psychiatric disturbances. Symptoms are attributed to cell death in the striatum and disruption of cortical-striatal circuitry. Mechanisms of cell death are unclear, but processes involving mitochondrial abnormalities, excitotoxicity, and abnormal protein degradation have been implicated. Many factors like… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
39
0

Year Published

2007
2007
2014
2014

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 55 publications
(39 citation statements)
references
References 108 publications
0
39
0
Order By: Relevance
“…Misfolded HTT aggregation causes selective neuronal loss, primarily in the cortex and striatum, and also can lead to cognitive and motor impairments. The repetition of glutamine residue in HTT is critical for its toxicity: that is as the number of CAG repeats increases (CAG: gene code for glutamine), the HTT deposition and neurotoxicity are greater [7981]. Interestingly, HSP70 is capable of preventing poly-glutamine-induced toxicity in HD models [82].…”
Section: Role Of Hsps In Different Neurodegenerative Diseasesmentioning
confidence: 99%
“…Misfolded HTT aggregation causes selective neuronal loss, primarily in the cortex and striatum, and also can lead to cognitive and motor impairments. The repetition of glutamine residue in HTT is critical for its toxicity: that is as the number of CAG repeats increases (CAG: gene code for glutamine), the HTT deposition and neurotoxicity are greater [7981]. Interestingly, HSP70 is capable of preventing poly-glutamine-induced toxicity in HD models [82].…”
Section: Role Of Hsps In Different Neurodegenerative Diseasesmentioning
confidence: 99%
“…Less than 1% of transplanted cells from autologous whole bone marrow transplanted into the striatum of an excitotoxic HD rat model expressed a neuronal marker [121]. However, functional recovery was seen in this study, and a survival advantage was observed in a separate study using human umbilical cord blood in a transgenic HD mouse model (reviewed in [122]). Further, in vitro proliferation of stem cells prior to transplantation, which should maximise their regenerative potential, may have a deleterious effect on graft survival if continued beyond four weeks (reviewed in [116]).…”
Section: Exogenous Cell Transplantmentioning
confidence: 73%
“…HD is a good candidate for cell transplantation therapy have prompted studies to evaluate the potential of alternative renewable cell sources for transplantation therapy because there is no effective treatment and there is the potential for early intervention. for HD (29,39,40). In particular, human embryonic stem undertaken 1 week after 50 nM QA lesioning (at coordinates AP +0.5 mm, ML +2.7 mm, DV −5.0 mm).…”
Section: Introductionmentioning
confidence: 95%